Glecaprevir/Pibrentasvir is safe and effective in Italian patients with chronic Hepatitis C aged 75 years or older: A multicenter study. (March 2023) - Pugliese, N.; Calvaruso, V.; Masarone, M.; D'Ambrosio, R.; Battistella, S.; Licata, A.; Persico, M.; Anolli, M.P.; Distefano, M.; Petta, S.; Russo, F.P.; Di Marco, V.; et al.
Abstract : Glecaprevir and Pibrentasvir (G/P) determines high rates of sustained virologic response (SVR) with optimal safety profile in patients with chronic hepatitis C virus (HCV) infection. The efficacy and safety of G/P in Caucasian patients aged 75 years and older has not been widely analyzed. This is a retrospective multicenter real-world study enrolling all consecutive patients 75 years and older who received G/P between October 2017 and January 2022 at 5 referral centers in Italy. SVR was analyzed by Intention to Treat (ITT) and Per Protocol analysis (PP). 570 patients met the inclusion criteria and were analyzed: mean age was 80 (75-97) years, 356 were females, 52% (298/570) had HCV-1 and 44% (252/570) had HCV-2. 137 (24%) patients had liver cirrhosis. 463 (81%) patients were taking at least 1 concomitant drug, with 144 (25%) taking ≥5 concomitant drugs. G/P was given for 8 weeks in 488 patients (86%). During treatment 48 patients (8%) reported side effects, with 10 (2%) patients discontinuing treatment prematurely. Two patients developed treatment unrelated serious adverse events. Overall, the SVR rate was 97.9% (558/570) by ITT analysis and 99.6% (558/560) by PP analysis. SVR rates remained consistently high among subgroup analysis stratified by genotype, treatment duration, fibrosis stage and concomitant medications. Treatment with G/P achieved 97.9% SVR rates in HCV patients older than 75 years of age. Safety was optimal with only 2% of patients discontinuing early.